Improved Backyard Chicken Varieties for Enhanced Poultry Production - R.Thangadurai (The Indian Veterinary Journal, 2026)
In the Indian rural economy, poultry farming plays a vital role in the socio-economic development of the downtrodden by generating valuable employment and income and providing protein rich diet relatively at a lower cost. This study was conducted during the period from 2017 to 2022. On-Farm Trials (OFTs) and Front-Line demonstrations (FLDs) were conducted in Dharmapuri, Salem and Vellore districts to assess the productive and reproductive traits of improved chicken varieties (Srinidhi, Gramapriya, Nandanam Broiler-3, TANVAS Aseel, and Vanashree) under backyard conditions. Data were gathered on the mean body weights at different age groups, feed consumption, mortality, livability, age at first egg production, annual egg production, hatchability, fertility and monthly income. Body weight, egg production, and hatchability were lower in local chicken, compared to Srinidhi, Gramapriya, Nandanam Broiler-3, TANUVAS Aseel, and Vanashree strains. However, no differences were observed between these improved chicken varieties. Srinidhi chicken and TANUVAS Aseel chicken for egg production and meat production, respectively, were identified as suitable strains in the study areas of Vellore district. The annual egg production was 168.23 ± 1.98 in Srinidhi chicken, and the meat production in TANUVAS Aseel chicken was 2156.12 ± 1.89 kg.